The effect of dexmedetomidine on the vagolytic effect of pancuronium during propofol induction - Lapisatepun, Worawut; Pipanmekaporn, Tanyong; Threesuthacheep, Chalermkiat; Wisadekarn, Kanchana (Biomedical Sciences and Clinical Medicine, 2017)
Objective To determine the effect of dexmedetomidine on the vagolytic effect of pancuronium during propofol induction and the hemodynamic responses to intubation in normotensive patients plus the effects of dexmedetomidine on the action of pancuronium Methods Forty-four American Society of Anesthesiologists (ASA) class I and II adults were included in this randomized, double-blind controlled trial. Patients with hypertension or preexisting bradycardia/tachycardia were excluded from the study. On arrival at the operating room, participating patients received a 20 ml infusion of either saline (Group C, n=22) or Dexmedetomidine 0.7 μg/kg (Group D, n=22) over a period of 10 minutes followed by propofol induction. Calibration of the twitch response of the adductor pollicis muscle was then performed followed by injection of pancuronium 0.12 mg/kg. Endotracheal intubation was accomplished 2.5 minutes after the injection. Initial blood pressure (BP) and heart rate (HR) were measured and recorded for baseline control. BP and HR were measured again at completion of drug infusion, 2.5 minutes after pancuronium, immediately after intubation, and then each minute for the next 5 minutes for a total of 5 times (T0-T5). Also recorded was the twitch height of the adductor pollicis muscle at the time of intubation and the duration of action of pancuronium. Results The HR in Group D was lower than that of Group C at 2.5 minutes after pancuronium (75.7±9.3 vs 88±12.9 bpm, p=0.013) but not different from its baseline. After intubation, HR at T0-T5 were comparable between groups. BP did not differ signi fi cantly between the groups during the entire study. In Group C, however, systolic BP at just before intubation was signi fi cantly lower than baseline (106.4±12.0 vs 121.0±13.9 mmHg, p=0.001). None of the patients needed treatment for hypo/hypertension or brady/tachycardia. At the time of intubation, Group D had a higher percentage of patients with a twitch height <10% than Group C (92 vs 67%, p=0.048). The duration of action of pancuronium was not different between the groups. Conclusions In normotensive patients, dexmedetomidine 0.7μg/kg infusion prior to propofol induction effectively reduces the vagolytic effect of pancuronium prior to intubation but does not blunt the blood pressure responses to intubation. It also quickens the onset of pancuronium but has no effect on its duration. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />